The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1046/j.1365-2222.1998.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide, a novel immunomodulating agent, prevents the development of allergic sensitization in an animal model of allergic asthma

Abstract: These data suggests that leflunomide can prevent primary allergic sensitization and prevent allergen-induced EAR by inhibiting production of allergen-specific IgE antibodies. Further studies in atopic conditions are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…We have previously shown that during treatment with leflunomide OA‐specific IgE and IgG production are reduced to levels equivalent to those of naive, nonsensitised control animals [ 15]. All isotypes tested of OA‐specific IgG were equally effected whilst total IgG levels were not.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We have previously shown that during treatment with leflunomide OA‐specific IgE and IgG production are reduced to levels equivalent to those of naive, nonsensitised control animals [ 15]. All isotypes tested of OA‐specific IgG were equally effected whilst total IgG levels were not.…”
Section: Discussionmentioning
confidence: 97%
“…We have demonstrated here that leflunomide treatment reduces IgE production and therefore, presumably, IgE activation of mast cells. We have previously shown that IgE dependent mast cell degranulation is inhibited in vitro by leflunomide via prevention of synthesis of allergen‐specific IgE [ 15]. Mast cell mediators are also known to have an effect on the integrity of the endothelial barrier through which these cells pass when migrating from the blood stream into the lung.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leflunomide was developed originally as an anti-inflammatory drug, but was found to be far more active against a wide range of immune disorders in murine models. These models include asthma, SLE, chronic graft versus host disease, autoimmune tubulointerstitial nephritis, anti-basement membrane glomerulonephritis, allergic encephalomyelitis, autoimmune uveitis, and anti-allograft and anti-xenograft rejection (Eber et al, 1998;Waer, 1996;Wennberg et al, 1997;Xu et al, 1997;Yeh et al, 1996Yeh et al, , 1997. The drug significantly decreases disease-specific antibody formation.…”
Section: Leflunomidementioning
confidence: 99%